Effect of Sintering Temperature on the Properties of Aluminium-Aluminium Oxide Composite Materials - Nuruzzaman, D. M.; Farah Fazira, Kamaruzaman; NasrahAzmi, Mohd Azmi (deerhillpublishing, 2016)
In this study, aluminium-aluminium oxide (Al-Al2O3) metal matrix composites of different weight percentage reinforcements of aluminium oxide were processed at different sintering temperatures. In order to prepare these composite specimens, conventional powder metallurgy (PM) method was used. Three types specimens of different compositions such as 95%Al+5%Al2O3, 90%Al+10%Al2O3 and 85%Al+15%Al2O3 were prepared under 20 ton compaction load. Then, all the specimens were sintered in a furnace at two different temperatures 550oC and 580oC. In each sintering process, two different heating cycles were used. After the sintering process, it was observed that undistorted flat specimens were successfully prepared for all the compositions. The effects of sintering temperature and weight fraction of aluminium oxide particulates on the density, hardness and microstructure of Al-Al2O3 composites were observed. It was found that density and hardness of the composite specimens were significantly influenced by sintering temperature and percentage aluminium oxide reinforcement. Furthermore, optical microscopy revealed that almost uniform distribution of aluminium oxide reinforcement within the aluminium matrix was achieved.